2020
DOI: 10.1590/0100-29452020417
|View full text |Cite
|
Sign up to set email alerts
|

Estimating leaf area of prata-type banana plants with lanceolate type leaves

Abstract: Models for estimating leaf area of bananas found in the literature are not suitable for lanceolate type leaves occurring at the vegetative stage of ratoon suckers dependent of mother plant. The objective was to determine equations for estimating the leaf area of ‘Prata-Anã’ and ‘BRS Platina’ banana plants with lanceolate type leaves. 212 and 164 lanceolate type leaves having 10 cm-wide lamina or less were collected from ‘Prata-Anã’ and ‘BRS Platina’ banana plants of 90 days of age or less, respectively. Width … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Thus, the present study's sample size (number of leaves = 300) is adequate for estimating the leaf area of T. populnea using linear dimensions of the leaf limbs. Other research has also recorded greater variability for the product between length and width (Gomes et al 2020), the product between length and length (Ribeiro et al 2020b), the product between width and width (Oliveira et al 2019b), and observed leaf area (Donato et al 2020). The kurtosis coefficients of the variables of the present study showed that the frequency distribution was flatter than the normal distribution (Ribeiro et al 2020a).…”
Section: Discussionsupporting
confidence: 55%
“…Thus, the present study's sample size (number of leaves = 300) is adequate for estimating the leaf area of T. populnea using linear dimensions of the leaf limbs. Other research has also recorded greater variability for the product between length and width (Gomes et al 2020), the product between length and length (Ribeiro et al 2020b), the product between width and width (Oliveira et al 2019b), and observed leaf area (Donato et al 2020). The kurtosis coefficients of the variables of the present study showed that the frequency distribution was flatter than the normal distribution (Ribeiro et al 2020a).…”
Section: Discussionsupporting
confidence: 55%
“…Our review explicated that most of the developed models are linear. Many authors have developed simple linear and/or MLR equations to estimate banana productivity (Potdar and Pawar, 1991; Wairegi et al ., 2009; Zucoloto et al ., 2013; Alcudia-Aguilar et al ., 2019; Olivares et al ., 2020), and growth (Potdar and Pawar, 1991; Demirsoy, 2009; Nyombi, 2010; Vinson et al ., 2018; Donato et al ., 2020). In all these models, the growth and yield of bananas have been modelled as a function of either plant characteristics or weather, soil, and/or management practices by integrating agronomic knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…4. A more realistic leaf area estimation model was developed by Donato et al (2020) for 'Prata-Ana' and 'BRS Plantina' banana plants using the variables width (W ), length (L) and width/length ratio (WLR). The following models gave precise results (R 2 around 0.96, and R = 0.98, respectively): LA (Prata-An a ) = −0.0133624 + 0.000489859L + 0.00183182W (4) LA (Platina) = 0.00237026 + 0.00478116 W − 0.0968020WLR…”
Section: Modelling Of Banana Growthmentioning
confidence: 99%
“…Diverse methods have been utilized to determine leaf area, including destructive and nondestructive methods, and allometric models have been described for estimating leaf area including a nondestructive approach that reduces time required and other costs (JONCKHEERE et al 2004). However, existing models have demonstrated limitations when utilized for different genotypes of bananas or in plants cultivated under conditions of biotic or abiotic stress (ZUCOlOTO et al 2008;DONATO et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…During the development of banana plants there is a change in the shape of leaves that reflects the transition from an initial vegetative stage of slow growth of the plant to a stage of rapid growth. The alteration in the form of the leaves signals the end of the hormonal inhibition of production of suckers by the mother plant (DONATO et al 2020). The form and extent of these changes have a strong relationship with the plant cultivar or genotype and the edaphoclimatic conditions under which the plants are cultivated, requiring adjustments in methods and models for estimation of the leaf area for new cultivars that have been developed (TURNER, 1998;2003).…”
Section: Introductionmentioning
confidence: 99%